Pentingnya Klasifikasi Customer Sebelum Melakukan Perancangan Strategi Digital Marketing - Iasa Nur Firdausi; Siti Ning Farida (Universitas Kristen Indonesia Toraja, 2023)
The failure of the digital marketing campaign at PT Lentera Alam Nusantara is the author's background for researching the best solutions before designing a digital marketing strategy. This research journal aims to measure and prove how important customer classification is as a basis for designing digital marketing strategies in the hope of minimizing campaign failures. The research was conducted descriptively using a qualitative approach to gather information and provide a detailed description of the phenomenon. The research findings prove that there is a significant positive influence on the results of strategy implementation after customer classification. Thus it can be interpreted that the author's hypothesis about the importance of customer classification before designing a digital marketing strategy at PT Lentera Alam Nusantara can be proven by the results of the research.